Kemampuan Pemahaman Konsep Matematis: Sebuah Kajian Literatur - Dwi Jeanita Sengkey; Pinta Deniyanti Sampoerno; Tian Abdul Aziz (Griya Journal of Mathematics Education and Application, 2023)
This study discusses the meaning and indicators of mathematical understanding concepts. The research method used is library research. Based on the results of the study, it was found that the ability to understand a concept mathematically is the ability to absorb and understand an idea or mathematic concept and relates one concept to another, and being able to represent it with mathematic form and create mathematic problem-solving algorithms in a precise, accurate and efficiently applied in everyday problems using own language.